Impressive response to denosumab in a patient with bone metastatic adenocarcinoma of the stomach after 2 years of zoledronic acid. Issue 2 (February 2015) - Cappetta, Alessandro; Spano, Laura; Evangelista, Laura; Zovato, Stefania; Opocher, Giuseppe; Pastorelli, Davide
<x xml:space="preserve">Abstract</x> Bone is a common site for tumor spread in patients with solid tumors. So far bisphosphonates have been the main pharmacological treatment option for patients with bone metastases. We present a case of bone metastatic gastric cancer treated with zoledronic acid at first and later with denosumab. After 1 year of denosumab treatment, the 18F-fluorodeoxyglucose (18F-FDG)-PET/computed tomography scan reassessment documented a metabolic complete response, even in the absence of specific antiblastic treatment. Whether denosumab can be used directly after pretreatment with bisphosphonates has yet to be addressed.